Public education and economic prosperity: Semi-endogenous growth revisited - Klaus Prettner (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2012)
We introduce publicly funded education into R&D-based economic growth theory. Our framework allows us to i) explicitly describe a realistic process of human capital accumulation within these types of growth models, ii) reconcile semi-endogenous growth theory with the empirical evidence on the relationship between economic development and population growth, and iii) revise the policy invariance result of semi-endogenous growth frameworks. In particular, we show that the model supports a negative association between economic growth and population growth if the education sector is well developed and the population growth rate is low, that is, for modern industrialized countries. Furthermore, within our framework, changes in public educational investments have the potential to affect the long-run balanced growth rate.
Keywords: I25; J24; O11; O31; O41; 330; public education; human capital accumulation; technological change; semi-endogenous economic growth